1978
DOI: 10.1021/j100492a001
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of formaldehyde-butene mixtures at low pressures. Quantum yield of radical decomposition process in formaldehyde

Abstract: The feasibility of measuring the H-atom quantum yield ( ) in the photolysis of H2CO by the + cis-2-butene and + 1-butene addition reactions below 1 Torr has been studied. This chemical trapping method provides fairly reliable results below ~300 nm. The single vibronic level values of extrapolated to zero-pressure are 0.68 ± 0.10 at 275.4 nm, ~0.6 at 288.2 nm, and 0.68 ± 0.05 at 303.5 nm. These values are in good agreement with the very recent values of Horowitz and Calvert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…02CH20H -* (H02CH20) -H02 + CH20 (14) If reaction 14 as well as 7 occurs then in theory the fraction of 02CH20H radicals formed in (7) which ultimately lead to H02CH20H product in (8) should increase with increasing [H02] in the experiments at high [Cl2], Thus the apparent rate of H02 addition to CH20 would be increased with [Cl2] increase as we observe in the plot of Figure 7.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…02CH20H -* (H02CH20) -H02 + CH20 (14) If reaction 14 as well as 7 occurs then in theory the fraction of 02CH20H radicals formed in (7) which ultimately lead to H02CH20H product in (8) should increase with increasing [H02] in the experiments at high [Cl2], Thus the apparent rate of H02 addition to CH20 would be increased with [Cl2] increase as we observe in the plot of Figure 7.…”
Section: Discussionmentioning
confidence: 65%
“…We may check on the consistency of the present experimental estimates of the rate constants fe7 and fe14 by using thermochemical methods. H02 + CH20 ^02CH20H (7,14) From Benson's additivity rules we can estimate that °-16.8 kcal/mol and AS7°^-32.7 eu (25 °C, 1 atm standard state).21 From these we calculate fe7/fe14 = g-w/RTg^/R " 1-5 x i05 atm-1 = 0.15 ppm-1 (25 °C). This checks well with the ratio of the experimental kinetic estimates of the individual constants: fe7/fe14 = 0.17 ppm-1.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…HNO + 2NO -N2 + HN03 (10) 2HNO -H20 + N20 (11) studies_have shown that the electronically excited HNO*(A1 A") is formed by a three-body process (5a), but we haved added a two-body mechanism (4a) for the sake of completeness. Although the lifetime of HNO* has not been measured directly, it has been estimated to be in the order of <10-7 s in the chemiluminescent system,23 since (010)-( 000) and (001)-(000) emission bands near 700 nm have been observed.13 Since the formation of HNO* by the recombination of HCO and NO is quite endothermic, it is sufficient to consider the lower energy product channel (reaction 9) only.…”
Section: Resultsmentioning
confidence: 99%
“…is j ¼ 0.8 at 308 nm as obtained by Moortgat and Warneck. 25 Alternative investigations of j, which resulted in 0.68 < j < 0.7, [28][29][30] were also discussed and reevaluated by Moortgat and Warneck. Other reactions that are important for the formaldehyde system include: 6,[31][32][33][34][35][36][37]…”
Section: Introductionmentioning
confidence: 99%